Chlorophyll Fluorescence Emissions of Vegetation Canopies From High Resolution Field Reflectance Spectra - Middleton, E.; Corp, L.; Daughtry, C.; Campbell, Petya Entcheva (IEEE, 2007)
A two-year experiment was performed on corn (Zea mays L.) crops under nitrogen (N) fertilization regimes to examine the use of hyperspectral canopy reflectance information for estimating chlorophyll fluorescence (ChlF) and vegetation production. Fluorescence of foliage in the laboratory has proven more rigorous than reflectance for correlation to plant physiology. Especially useful are emissions produced from two stable red and far-red chlorophyll ChlF peaks centered at 685±10 nm and 735±5 nm. Methods have been developed elsewhere to extract steady state solar induced fluorescence (SIF) from apparent reflectance of vegetation canopies/landscapes using the Fraunhofer Line Depth (FLD) principal. Our study utilized these methods in conjunction with field-acquired high spectral resolution canopy reflectance spectra obtained in 2004 and 2005 over corn crops, as part of an ongoing multi-year experiment at the USDA/Agriculture Research Service in Beltsville, MD. SIF intensities for ChlF were derived directly from canopy reflectance spectra in specific narrow-band regions associated with atmospheric oxygen absorption features centered at 688 and 760 nm. The N treatments accounted for 80% of the variation in the foliar C/N ratios, which declined from ~23 in the lowest N treatment to ~14 at the highest N treatment. A leaf-level steady state fluorescence ratio, Fs/Chl, was positively related to foliar C/N ratio (r² = 0.84, n=102). Similarly, the red/far-red SIF ratio derived from the field reflectance spectra was positively related to the foliar C/N ratio (r² = 0.64, n = 109). Both fluorescence ratios were inversely, and non-linearly correlated with crop grain yield (Kg / ha) determined at harvest a month later (Fs/Chl ratio, r = 0.92; SIF Red/Far-Red ratio, r = 0.85). This study has relevance to future passive satellite remote sensing approaches to monitoring C dynamics from space.
2006 IEEE International Symposium on Geoscience and Remote Sensing, 31 July 2006 - 04 August 2006, Denver, CO, USA